Digital Sisterhood di Era Post-Feminisme: Analisis Keterlibatan Komunitas dalam Membangun Ruang Aman bagi Perempuan pada Platform Instagram @condfe - Festyanove Hapsari Ramadian Nugraheni; Lukman Hakim (Journal of Creative Student Research, 2026)
The evolution of the digital landscape has triggered a significant shift in the expression of female agency on social media. This study aims to analyze how the Instagram account @condfe constructs a safe space for women through community engagement strategies and “coquettish” (centil) aesthetic narratives. Amidst the ambivalence of social media, which often becomes a toxic space for judgment, objectification, and cyberbullying against women, @condfe reconstructs the meaning of femininity from a ost-feminism perspective. Using a descriptive qualitative approach with thematic analysis methods, this research dissects the visual content and textual interactions within the comment section of @condfe. The results indicate that @condfe successfully builds a digital sisterhood through the practices of mutual compliments, daily tip-sharing, and intense horizontal emotional support. These findings show that highly feminine visual aesthetics and participatory horizontal interactions on social platforms are not merely decorative but play a significant role in creating emotional attachment and female agency. The @condfe account functions not only as a lifestyle content curation platform but also acts as a community builder that provides subtle advocacy for women’s rights and raises awareness of sexual violence in the digital era. This study highlights the importance of supportive cyber ecosystems.